Quantitative Assessment of Sensory Integration and Balance in Children with Autism Spectrum Disorders: Cross-Sectional Study - Mohamed A. Abdel Ghafar; Osama R. Abdelraouf; Abdelgalil A. Abdelgalil; Mohamed K. Seyam; Rafik E. Radwan; Amira E. El-Bagalaty (MDPI AG, 2022)
Postural stability is dependent on the interpretation of external inputs acquired by sensory information processes, such as visual, vestibular, and proprioceptive systems, in order to accomplish neuromuscular control, balance maintenance, and appropriate motor response. A defect in any of these systems, or in the integration of information given by these systems, might threaten their capacity to maintain balance. Therefore, the purpose of this study was to investigate the sensory integration and balance using the Biodex balance system (BBS) in children with autism spectrum disorder (ASD) during the static posture. Seventy-four children from both sexes, 38 with ASD matched with 36 typically developed (TD) children as a control group, were included in the study. Using the Biodex balance system, the postural sway was evaluated through the modified Clinical Test of Sensory Integration and Balance (m-CTSIB) during quiet standing. In this test, four different situations were considered from standing position: eyes open/firm surface, eyes closed/firm surface, eyes open/foam surface, and eyes closed/foam surface. ASD children showed a significant increase in postural sway under all tested conditions when compared to the TD children group, especially for the conditions in which visual and somatosensory inputs were disrupted (p-value < 0.05). These results provide evidence that postural stability decreased in ASD children. Under static postural challenges, the current study's findings imply that children diagnosed with ASD have postural control deficiencies, especially for the conditions in which visual and somatosensory input was disrupted. Further research must be conducted to find the best balance training program for ASD cases using the Biodex balance system and considering its impact on motor skills.